Modified template synthesis and electrochemical performance of a Co3O4/mesoporous cathode for lithium–oxygen batteries - Wang, S.; Sha, Y.; Zhu, Y.; Xu, X.; Shao, Zongping (Royal Society of Chemistry, 2015)
Rechargeable lithium–oxygen batteries (LOBs) with much higher energy density than conventional lithium-ion batteries are supposed to be the next generation of electrochemical energy storage devices. The oxygen electrode is the key component that determines the capacity and cycling performance of this type of battery. In this study, a Co3O4/mesoporous carbon composite (Co3O4/C) with a carbon content of 42 wt%, a rich mesoporous pore content and a homogeneous distribution of Co3O4 nanoparticles over the carbon surface was prepared using a facile silica template method with sucrose as the carbon source, and H3BO3 as an agent for expanding the space between the silica and carbon to impregnate and accommodate the Co3O4 precursor. This composite was used directly as the oxygen electrode in LOBs without additional conductive carbon additives. Galvano charge–discharge tests showed that the capacity of the composite electrode based on the mass of the mesoporous carbon reached approximately 4500 mA h gcarbon−1 at a current density of 123 mA gcarbon−1. The cell was further successfully run for over 200 discharge–charge cycles at a fixed current density of 246 mA gcarbon−1 and a trapped capacity of 740 mA h gcarbon−1, which indicated the superior electrochemical performance of the electrode. Different materials have been comparatively tested as oxygen electrodes, including Super P (SP), SP + nano Co3O4, carbon derived from KIT-6 (KIT-6-C), and the as-prepared Co3O4/C, among which the current Co3O4/C composite showed the best performance. The proposed Co3O4/C material has significant potential as an electrode material for rechargeable Li–O2 batteries.